2014
DOI: 10.2967/jnumed.114.138701
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Antagonist Radiotracer for the κ-Opioid Receptor: Synthesis and Characterization of 11C-LY2459989

Abstract: The kappa opioid receptors (KOR) are implicated in a number of neuropsychiatric diseases and addictive disorders. Positron Emission Tomography (PET) with radioligands provides a means to image the KOR in vivo and investigate its function in health and disease. The purpose of this study was to develop the selective KOR antagonist 11C-LY2459989 as a PET radioligand and characterize its imaging performance in non-human primates. Methods LY2459989 was synthesized and assayed for in vitro binding to opioid recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…209 Furthermore, this strategy and method for radiolabeling has proven useful in development of a second-generation KOR antagonist PET radiotracer with improved KOR selectivity and binding, [ 11 C]LY2459989. 210 …”
Section: [11c]hcn Cyanationmentioning
confidence: 99%
“…209 Furthermore, this strategy and method for radiolabeling has proven useful in development of a second-generation KOR antagonist PET radiotracer with improved KOR selectivity and binding, [ 11 C]LY2459989. 210 …”
Section: [11c]hcn Cyanationmentioning
confidence: 99%
“…Previous studies with KOR radiotracers indicated that cerebellum can be used as a reference region in nonhuman primates to calculate BP ND (44). This appeared to be true as well for 11 C-EKAP, as cerebellum V T remained similar when various blocking drugs were administered and regional BP ND values estimated by SRTM using cerebellum as the reference region exhibited an…”
Section: Discussionmentioning
confidence: 57%
“…pharmacologically (Lowe et al, 2014) and some as KOR radiotracers for PET (Zheng et al, 2013(Zheng et al, , 2014. LY2795050 has been evaluated as an antagonist PET tracer in both NHPs (Zheng et al, 2013;Kim et al, 2013) and humans (Naganawa et al, 2014b(Naganawa et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%